Sea state conditions for marine structures' analysis and model tests. (1st June 2016) - Bitner-Gregersen, Elzbieta M.; Dong, Sheng; Fu, Thomas; Ma, Ning; Maisondieu, Christophe; Miyake, Ryuji; Rychlik, Igor
Abstract: The study reviews, based on the state-of-the-art findings, some uncertainties associated with wave data and models currently used in design and operation procedures of ship and offshore structures. Although the same basic principles prevail for hydrodynamic loads on ships and offshore structures, actual problems and methods for assessing these loads in the design and operation stage are not the same. Different wave data and models are used for specifying design and operational criteria for these two types of platforms and different uncertainties are related to them. Wave data and models used to define sea state characteristics are discussed and particular attention is given to the associated sources of uncertainties. Some weaknesses of wave input used in design and operational procedures for marine structures are pointed out. Focus is also given on uncertainties related to model tests as tank testing is an important supporting tool for design and operation. Impact of some selected uncertainties on wave description and wave loads is demonstrated by examples. Highlights: Definitions of uncertainties. Establishment of sea state characteristics for marine structures' analysis and model tests. Uncertainties associated with sea state characteristics. Impact of uncertainties of sea state characteristics on model tests and design and operations of marine structures.